Survival outcomes of patients with diffuse large B-cell lymphoma undergoing autologous stem cell transplantation in Germany: real-world evidence from an administrative database between 2010 and 2019 - Heger, Jan-Michel; Borchmann, Peter; Riou, Sybille; Werner, Barbara; Papadimitrious, Michael S.; Mahlich, Jörg (Frontiers in Oncology, 2024)
BackgroundLimited real-world evidence is available for patients with diffuse large B-cell lymphoma (DLBCL) who received an autologous stem cell transplantation (ASCT) in Germany.ObjectivesThis study aims to describe the real-world survival outcomes of patients with DLBCL who received ASCT in Germany after diagnosis.DesignThis study is a retrospective database analysis covering the period between 2010 and 2019.MethodsUnadjusted overall survival (OS) was plotted using the Kaplan–Meier estimator for the overall population and stratified by relapse status. A Cox regression was run to identify factors that influence OS.ResultsA total of 112 patients received an ASCT, with the average time from first-line treatment to ASCT being 11.7 months. The median OS estimated by Kaplan–Meier was 83.4 months for the entire cohort. The only variable that significantly reduced the OS was the presence of subsequent treatment after ASCT in a time-dependent model.ConclusionOS after ASCT for DLBCL patients in Germany is higher than previously reported and may still be considered a valid option for carefully selected patients with relapsed/refractory DLBCL.